Inflation measurement and its assessment in the ECB's monetary policy strategy review (European Central Bank (ECB), 2021)
This paper - which takes into consideration overall experience with the Harmonised Index of Consumer Prices (HICP) as well as the improvements made to this measure of inflation since 2003 - finds that the HICP continues to fulfil the prerequisites for the index underlying the ECB's definition of price stability. Nonetheless, there is scope for enhancing the HICP, especially by including owner-occupied housing (OOH) using the net acquisitions approach. Filling this long-standing gap is of utmost importance to increase the coverage and cross-country comparability of the HICP. In addition to integrating OOH into the HICP, further improvements would be welcome in harmonisation, especially regarding the treatment of product replacement and quality adjustment. Such measures may also help reduce the measurement bias that still exists in the HICP. Overall, a knowledge gap concerning the exact size of the measurement bias of the HICP remains, which calls for further research. More generally, the paper also finds that auxiliary inflation measures can play an important role in the ECB's economic and monetary analyses. This applies not only to analytical series including OOH, but also to measures of underlying inflation or a cost of living index.
Keywords: C43; C52; C82; E31; E52; 330; Monetary policy review; HICP inflation; inflation measurement; owneroccupied housing; measurement bias; underlying inflation